Tuntutan Pekerja Terhadap Hak Maternitas Bagi Tenaga Kerja Wanita Hamil yang Tidak di Penuhi Secara Keadilan Ditinjau Dari Perspektif Hukum Kesehatan dan Keselamatan Kerja (Studi Kasus PT. Alpen Food Industry Bekasi) - Nopianti, Wike; Setiady, Tri; Abas, Muhamad (LPPM Universitas Ekasakti Padang, 2024)
Problems that arise due to the increasing number of female workers, ranging from issues of gender equality, health, legal protection and wages. The 2000 Indonesian Occupational Health and Safety (K3) training document explains that for certain chemicals, conditions in factories such as excessive heat. In this research, researchers focused on the problems that existed when the research was carried out, secondary data related to reviewing maternity rights for pregnant women workers in ensuring the safety and health of pregnant women and the fetuses they contain. Article 86 paragraph (1) of the Manpower Law emphasizes: every worker has the right to obtain protection for occupational safety and health (K3) where pregnant female workers can ask to do work that is not heavy and dangerous. PT. This AFI violates existing legislation where pregnant women workers are employed on night shifts in accordance with the Company's operations without paying attention to Occupational Health and Safety, but the author provides a strategy to increase the fulfillment of maternity rights for pregnant women workers at PT. AFI's first step involves understanding the company's understanding of the applicable legal framework, including Law Number 13 of 2003 concerning Employment, which regulates the protection of female workers, including maternity rights.